The Utilization of the Canva Application Arabic Learning at Baiturrahman - Muhammad Husni Shidiq; Luqman MoHa; Adam Mudinillah (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Learning Arabic is often considered difficult and uninteresting by some students. This encourages educators to look for innovative ways to increase students' interest in learning. One way that can be done is to utilize technology in learning, one of which is the Canva application. Canva is an online application that can be used to design various learning media with a variety of attractive templates, as well as a variety of shapes, images, colors, and fonts. Purpose. This study aims to describe the use of the Canva application as an effort to increase students' interest in learning Arabic. Through the use of Canva, it is hoped that students can be more interested and motivated in learning Arabic, especially in the context of distance learning. Method. This research uses library research methods. The literature sources used are journals and books relevant to this research topic. The analysis was conducted by reviewing various literature sources that discuss the use of Canva applications in the development of learning media, especially e-modules for Arabic. Results. The results showed that the Canva app can be used to create attractive e-modules for students. The process of using it includes creating a Canva account, designing modules, selecting and editing backgrounds, adding text, and downloading or sharing design results. By using Canva, students can produce more interesting Arabic teaching materials, so learning becomes more interactive and fun. Conclusion. The use of the Canva application in making e-modules can increase students' interest in learning Arabic. An attractive and interactive design can make learning materials more lively and not boring, especially in the context of distance learning. Therefore, Canva can be one of the innovative solutions in the development of effective learning media.